Mode of action of T cells engineered with CAR or TCR for cancer treatment - Kobold, Sebastian (Henry Stewart Talks, 2020)
Introduction to therapeutic use T cells, Clinical use of CAR T cell therapy, The mode of action of CAR T cell therapy, Differences to TCR T cell therapy, Resistance mechanisms to CAR T cell therapy